Model Tanaman Pangan-Ternak: Diversifikasi Pencaharian di Pedesaan - Heryanto, Mahra Arari; Nugraha, Adi (Universitas Galuh, 2024)
Diversification of livelihood is a commonly strategy apllied by rural communities for coping with economic and environmental pressures in poverty reduction. The poverty rate of rice smallholder is the highest compared to other sub-sectors. In this paper, we have explored and simulated smallholders households improving their welfare through non-rice additional income through livestock. Qualitatively-inductive exploration was held in Gabuswetan, Indramayu, West Java. Meanwhile, the quantitatively-deductive simulation is developed using system dynamics modeling. Analysis showed that high-value livelihoods through livestock can smallholders income and welfare. But, improving household welfare requires a long yearly delay because it is limited by the livestock rearing cacpacity and livestock purchasing and selling ability. During delay process, smallholders welfare have been decreased because of their economic resources are spent a lot in livestock purchasing. However, this delay process can be shortened by speeding up of livestock buying and selling turnover and increasing livestock capacity that being kept.